Diverse Anti-Tumor Immune Potential Driven by Individual IFNα Subtypes - Buzzai, Anthony C.; Wagner, Teagan; Audsley, Katherine M.; Newnes, Hannah V.; Barrett, Lucy W.; Barnes, Samantha; Wylie, Ben C.; Stone, Shane; McDonnell, Alison; Fear, Vanessa S.; Foley, Bree; Waithman, Jason (Frontiers in Immunology, 2020)
Immunotherapies harnessing T cell immunity have shown remarkable clinical success for the management of cancer. However, only a proportion of patients benefit. The presence of type I interferon (IFN) within the tumour microenvironment is critical for driving effective tumour-specific T cell immunity. Individuals can produce 12 distinct subtypes of IFNα, which all signal through a common receptor. Despite reported differences in anti-viral potencies, the concept that distinct IFNα subtypes can improve anti-cancer treatments remains unclear. We tested whether expression of unique IFNα subtypes confined to the tumour microenvironment enhances tumour control. This was systematically evaluated by transplantation of B16 murine melanoma cells secreting five unique IFNα subtypes (B16_IFNα2; B16_IFNα4; B16_IFNα5; B16_IFNα6; B16_IFNα9) into a pre-clinical murine model. We show that IFNα2 and IFNα9 are the only subtypes capable of completely controlling tumour outgrowth, with this protection dependent on the presence of an adaptive immune response. We next determined whether these differences extended to other model systems and found that the adoptive transfer of tumour-specific CD8+ T cells engineered to secrete IFN9 delays tumour growth significantly and improves survival, whereas no enhanced survival was observed using T cells secreting IFN4. Overall, our data shows that the expression of distinct IFNα subtypes within the tumour microenvironment results in different anti-tumour activities, and differentially affects the efficacy of a cancer therapy targeting established disease.